2022
DOI: 10.1177/13596535221102690
|View full text |Cite
|
Sign up to set email alerts
|

Acquired HIV drug resistance among adults living with HIV receiving first-line antiretroviral therapy in Rwanda: A cross-sectional nationally representative survey

Abstract: Background We assessed the prevalence of acquired HIV drug resistance (HIVDR) and associated factors among patients receiving first-line antiretroviral therapy (ART) in Rwanda. Methods This cross-sectional study included 702 patients receiving first-line ART for at least 6 months with last viral load (VL) results ≥1000 copies/mL. Blood plasma samples were subjected to VL testing; specimens with unsuppressed VL were genotyped to identify HIVDR-associated mutations. Data were analysed using STATA/SE. Results Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Despite that, all provinces and locality types had HIVDR levels above 20%, ranging between 21.6% and 36.6% on provincial level and from Our study found that after adjusting for potential confounders, the ARV-exposed had higher odds of HIVDR compared to the ARV-negative PLHIV. Consistent with our ndings, a national survey in Rwanda also found that ART regimens were signi cantly associated with HIVDR [43]. In contrast, a Nigerian national survey observed a signi cant association between HIVDR and being ARV-negative [28].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Despite that, all provinces and locality types had HIVDR levels above 20%, ranging between 21.6% and 36.6% on provincial level and from Our study found that after adjusting for potential confounders, the ARV-exposed had higher odds of HIVDR compared to the ARV-negative PLHIV. Consistent with our ndings, a national survey in Rwanda also found that ART regimens were signi cantly associated with HIVDR [43]. In contrast, a Nigerian national survey observed a signi cant association between HIVDR and being ARV-negative [28].…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the 25-34 years old and ≥ 45 years old age groups had reduced odds of developing HIVDR compared to 15-24 years old age group. On the contrary, national surveys from Rwanda, Kenya, Tanzania, Uganda and Nigeria found no signi cant association between HIVDR and age [28,43]. In a Chinese study by Zhou et al [44], being ≥ 15 years old signi cantly predisposed individuals to higher odds of HIVDR.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In South Africa, about 23% of people living with HIV (PLHIV) experience an episode of viraemia during first-line antiretroviral therapy (ART) [1]. Persistent viraemia during ART in PLHIV is usually due to inconsistent adherence [2,3] or drug resistance [3][4][5] and increases the risk of virologic or treatment failure [6,7]. This often leads to a slower immune reconstitution [8] and a higher incidence of all-cause mortality [9][10][11].…”
Section: Introductionmentioning
confidence: 99%